Contribution of Glutathione Peroxidase to the Virulence of Streptococcus pyogenes - Brenot, Audrey (American Society for Microbiology, 2004)
Glutathione peroxidases are widespread among eukaryotic organisms and function as a major defense against hydrogen peroxide and organic peroxides. However, glutathione peroxidases are not well studied among prokaryotic organisms and have not previously been shown to promote bacterial virulence. Recently, a gene with homology to glutathione peroxidase was shown to contribute to the antioxidant defenses of Streptococcus pyogenes (group A streptococcus). Since this bacterium causes numerous suppurative diseases that require it to thrive in highly inflamed tissue, it was of interest to determine if glutathione peroxidase is important for virulence. In this study, we report that GpoA glutathione peroxidase is the major glutathione peroxidase in S. pyogenes and is essential for S. pyogenes pathogenesis in several murine models that mimic different aspects of streptococcal suppurative disease. In contrast, glutathione peroxidase is not essential for virulence in a zebrafish model of streptococcal myositis, a disease characterized by the absence of an inflammatory cell infiltrate. Taken together, these data suggest that S. pyogenes requires glutathione peroxidase to adapt to oxidative stress that accompanies an inflammatory response, and the data provide the first demonstration of a role for glutathione peroxidase in bacterial virulence. The fact that genes encoding putative glutathione peroxidases are found in the genomes of many pathogenic bacterial species suggests that glutathione peroxidase may have a general role in bacterial pathogenesis.